2021
DOI: 10.3390/psychiatryint2020014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Online Schooling, Screen-Based Activities, and Parent Coping in Canadian Children’s COVID-19-Related Trauma and Anxiety Symptoms

Abstract: This study investigated the effects of online schooling and screen-based activities on Canadian children’s COVID-19-related trauma and generalized anxiety symptoms and how parents’ coping strategies influenced these associations. The participants were 121 Canadian children aged from 7 to 12. Parents were asked to report on their children’s school attendance, screen-based activities, and trauma and generalized anxiety symptoms, as well as their own coping strategies during the COVID-19 pandemic. Online schoolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
9
0
1
Order By: Relevance
“…In sum, the results of this follow‐up study seem to be less situational and may reflect potential chronic effects of the COVID‐19 pandemic on adolescents' academic motivation. The findings are in line with several recent studies indicating that youth experienced a decrease in motivation toward schoolwork 10,11 as well as high levels of distress during the COVID‐19 pandemic 12‐18 . Consequently, it is likely that they had difficulties engaging in activities that, in normal circumstances, were salient to them.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In sum, the results of this follow‐up study seem to be less situational and may reflect potential chronic effects of the COVID‐19 pandemic on adolescents' academic motivation. The findings are in line with several recent studies indicating that youth experienced a decrease in motivation toward schoolwork 10,11 as well as high levels of distress during the COVID‐19 pandemic 12‐18 . Consequently, it is likely that they had difficulties engaging in activities that, in normal circumstances, were salient to them.…”
Section: Discussionsupporting
confidence: 90%
“…The findings are in line with several recent studies indicating that youth experienced a decrease in motivation toward schoolwork 10,11 as as high levels of distress during the COVID-19 pandemic. [12][13][14][15][16][17][18] Consequently, it is likely that they had difficulties engaging in activities that, in normal circumstances, were salient to them. It remains to be seen if these negative effects on adolescents' motivational resources will persist in time.…”
Section: Discussionmentioning
confidence: 99%
“…It is di cult to determine whether these changes are due to the pandemic, especially since motivation tends to decline as students progress through grades (Fredricks & Eccles, 2002;Jacobs et al, 2002;Paulick et al, 2013;Watt, 2004). However, as we already pointed out, several recent studies revealed that students' mental health has been negatively impacted by this pandemic (Guimond et al, 2021;Lane et al, 2021;Rogers et al, 2021;Rothe et al, 2021;Tang et al, 2021;Tardif-Grenier et al, 2021;Vaillancourt et al, 2021) and these ndings leave to think that their motivational resources were also negatively impacted.…”
Section: Discussionmentioning
confidence: 91%
“…Based on these results, the perceived benefit of keeping school-aged children with FXS in their daily routines and remaining in person for school and related services is clear. While online learning has been found to have similar academic effects to in-person learning for neurotypical children [ 10 ], this did not seem to be the case for children with FXS based on their parent’s reports. While results from this survey were able to provide a general understanding of the trends based on the impact of the pandemic on this population, this is hopefully only the beginning for studies on the pandemic impact for this and similar populations and limitations to these results provide clear opportunities for further exploration.…”
Section: Discussionmentioning
confidence: 98%